Electrochemical Determination of Vanillin in Cookies at Mediated AuNPs/GR Nanocomposites Modified Glassy Carbon Electrode - Si, Xiaojing; Han, Mei; Li, Wei; Bai, Chen; Xu, Xin; Xu, Jieming (Current Analytical Chemistry, 2022)
Background: Currently, carbon nanomaterials and carbon nanomaterials-based electrodes have illustrated significant electrocatalytic abilities. Methods: An electrochemical sensor was developed for vanillin using graphene (GR) decorated with gold nanoparticles (AuNPs) on a glassy carbon electrode (GCE) with two steps. AuNPs/GR/GCE, as the electrochemical sensor for determination of vanillin, included dropping GR onto the electrode and then electrodepositing AuNPs on GR/GCE. The structure and morphology of the synthesized nanocomposites (AuNPs/GR) on the electrode were confirmed by scanning electron microscopy (SEM). Results: Electrochemical studies revealed that modification of the electrode surface with AuNPs/GR nanocomposites significantly increases the oxidation peak currents of vanillin. The peak currents in differential pulse voltammetry (DPV) of vanillin increased linearly with their concentration in the range of 5-120 μM. The limit of detection was found to be 1.7 μM for vanillin. Also, the effect of some interfering compounds, such as NaCl, KCl, glucose, alanine, phenylalanine, glycine, and others, on the determination of vanillin was evaluated, and none of them had a significant effect on the assay recovery. Conclusions: A new electrochemical biosensor was fabricated with AuNPs/GR nanocomposites. The sensor was successfully used to detect vanillin in cookie samples.
Keywords: graphene